2017
DOI: 10.1111/resp.13212
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of obstructive sleep apnoea

Abstract: Obstructive sleep apnoea (OSA) is a common chronic disease and is associated with high social and economic costs. OSA is heritable, and there is evidence of both direct genetic contributions to OSA susceptibility and indirect contributions via 'intermediate' phenotypes such as obesity, craniofacial structure, neurological control of upper airway muscles and of sleep and circadian rhythm. Investigation of the genetics of OSA is an important research area and may lead to improved understanding of disease aetiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 109 publications
(173 reference statements)
0
62
2
Order By: Relevance
“… Plasma biomarkers to diagnose and risk stratify OSA: Biomarkers are being used increasingly to diagnose various conditions, for example plasma exosomes and microRNAs are being applied to OSA such that a clinician may ultimately be able to diagnose a patient with OSA based on a blood test . Moreover, these approaches may provide some insight into why a given patient has OSA and what is the risk of a particular complication. Genome sequencing for individuals to predict risk of OSA and risk of OSA complications: Genetics studies are also providing insight into OSA risk and mechanisms . Big data approaches are now being applied to sleep medicine by using huge sample size to answer important questions .…”
Section: New Diagnosticsmentioning
confidence: 99%
“… Plasma biomarkers to diagnose and risk stratify OSA: Biomarkers are being used increasingly to diagnose various conditions, for example plasma exosomes and microRNAs are being applied to OSA such that a clinician may ultimately be able to diagnose a patient with OSA based on a blood test . Moreover, these approaches may provide some insight into why a given patient has OSA and what is the risk of a particular complication. Genome sequencing for individuals to predict risk of OSA and risk of OSA complications: Genetics studies are also providing insight into OSA risk and mechanisms . Big data approaches are now being applied to sleep medicine by using huge sample size to answer important questions .…”
Section: New Diagnosticsmentioning
confidence: 99%
“…This underscores gaps in our knowledge of the pathophysiological pathways linking OSA to other diseases. 19,21 Pathophysiological pathways linking OSA to other diseases and factors that influence individual differences in susceptibility are poorly understood. While there are several effective treatments for OSA, including continuous positive airway pressure (CPAP), there appears to be substantial variation in overall clinical response and attenuation of cardiometabolic consequences, suggesting heterogeneity in both the etiology of the disease and susceptibility to its physiological disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…OSA is a complex, phenotypically heterogeneous disorder driven by both obesity-related factors and other mechanisms 1719 . A number of studies have observed that OSA has a heritable component, with a two-fold increased risk in first-degree relatives of individuals with OSA 2026 .…”
Section: Introductionmentioning
confidence: 99%
“…Given the high heritability of obesity and the strong relationship with OSA, it is important to note that studies indicate OSA familial aggregation is not simply due to association with obesity 21; 24 . Genomic variation is also associated with measures of OSA severity, like the apnea-hypopnea index (AHI) 19 . Furthermore, a number of syndromes with well-defined genetic causes are associated with increased prevalence of OSA (e.g., Achondroplasia 35 , Down syndrome 36; 37 , Marfan’s syndrome 38 , Prader-Willi syndrome 39 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation